2021
DOI: 10.1002/yea.3657
|View full text |Cite
|
Sign up to set email alerts
|

Predicted N‐terminal N‐linked glycosylation sites may underlie membrane protein expression patterns in Saccharomyces cerevisiae

Abstract: N‐linked glycosylation is one type of posttranslational modification that proteins undergo during expression. The following describes the effects of N‐linked glycosylation on high‐level membrane protein expression in yeast with an emphasis on Saccharomyces cerevisiae. N‐linked glycosylation is highlighted here as an important consideration when preparing membrane protein gene constructs for expression in S. cerevisiae, which continues to be used as a workhorse in both research and industrial applications. Non‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…GRP78 belongs to the HSP70 family and plays a major role as a chaperone for proper protein refolding due to the UPR and ER stress induction [79]. While GRP78 inhibition plays an important role in the mode of action of BOLD-100 [32,33,61], the ER stress-inducing activity of 2-DG is based on the prevention of the N-glycosylation of proteins, causing their improper folding and trafficking and leading to UPR induction [19,21,59,60]. We identified that HCTR cells display an overall decreased GRP78 expression as compared to parental cells, reflecting the GRP78 downregulating activity of BOLD-100, especially in response to protein damage stress [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRP78 belongs to the HSP70 family and plays a major role as a chaperone for proper protein refolding due to the UPR and ER stress induction [79]. While GRP78 inhibition plays an important role in the mode of action of BOLD-100 [32,33,61], the ER stress-inducing activity of 2-DG is based on the prevention of the N-glycosylation of proteins, causing their improper folding and trafficking and leading to UPR induction [19,21,59,60]. We identified that HCTR cells display an overall decreased GRP78 expression as compared to parental cells, reflecting the GRP78 downregulating activity of BOLD-100, especially in response to protein damage stress [33].…”
Section: Discussionmentioning
confidence: 99%
“…2-DG, based on glucose deprivation, is known to induce ER stress via the prevention of N-glycosylation of proteins, leading to improper folding and trafficking and, finally, induction of the UPR [19,59,60]. Likewise, BOLD-100 causes enhanced ER stress, at least in part by interfering with ER chaperone GRP78 expression [32,33,61].…”
Section: Hct116 and Hctr Cells Differ In Er Stress Response To 2-dg And Bold-100 Treatmentmentioning
confidence: 99%
“…O-linked glycosylation and N-linked glycosylation are the two most important forms of protein glycosylation ( Sun et al, 2021 ). Unlike the O-linked glycosylation, N-linked glycosylation is one type of biological processes that proteins undergo during de novo synthesis ( Xu et al, 2018 ; Karki et al, 2021 ; Tian et al, 2021 ). N-linked protein glycosylation mainly begins from endoplasmic reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%